Protocol of an open-label safety and feasibility pilot study of ketamine-assisted psychotherapy for methamphetamine use disorder (the KAPPA trial) - Jonathan Brett; Celia Morgan; Nadine Ezard; Brendan Clifford; Krista J Siefried; Robert May; Liam Acheson; Kathryn Fletcher; Harriet MacDonald; Gillinder Bedi; Alexandre Guerin; Elizabeth Knock; et al. (BMJ Open)
Introduction Methamphetamine use disorder is a significant public health concern. No pharmacological treatment options currently exist for methamphetamine use disorder, and psychotherapy is only moderately effective. Preliminary evidence suggests that ketamine-assisted psychotherapy produces sustained improvements in substance use and mental health symptomatology. In addition to direct antidepressant properties, ketamine is hypothesised to increase synaptogenesis and facilitate neuroplasticity, in turn prolonging and enhancing the effects of psychotherapy. Given the withdrawal-associated dysphoria and neurocognitive impairments characterising methamphetamine use disorder, ketamine-assisted psychotherapy may improve the efficacy of psychotherapy alone by addressing these features and facilitating therapeutic engagement. This pilot study aims to investigate the safety and feasibility (time taken to recruit sample, proportion of ineligible participants at pre-screening and screening, number of participants who complete four sessions of psychotherapy, retention rate over full duration of study, acceptability of the intervention) of subanaesthetic ketamine in combination with psychotherapy (cognitive behavioural therapy) for adults with methamphetamine use disorder. Changes in methamphetamine use, cravings and withdrawal, quality of life, and treatment satisfaction will also be explored.Methods and analysis This is an open-label, single-arm clinical trial. 20 adults meeting DSM-5-TR criteria for methamphetamine use disorder who are seeking to reduce or cease methamphetamine use will be enrolled in the study through a single-site specialist outpatient stimulant treatment service in inner Sydney (St Vincent’s Hospital, Sydney). A 4-week course with three subcutaneous ketamine doses (0.75 mg/kg to 0.9 mg/kg, titrated according to tolerability) at weekly intervals and four sessions of cognitive behavioural therapy (one at treatment initiation and three within 24–48 hours following each ketamine administration session) will be delivered. Safety and feasibility will be assessed over an 8-week period. Secondary outcomes (changes in methamphetamine use, cravings, withdrawal, quality of life and treatment satisfaction) will be assessed over a 24-week period.Ethics and dissemination This study has been approved by the St Vincent’s Hospital Human Research Ethics Committee, reference 2023/ETH00530. Study findings will be disseminated through articles in scientific, peer-reviewed journals, and at national and international conferences.Trial registration number ANZCTR: ACTRN12624000895583.Protocol version The trial protocol (Version 4.0) was approved on 24 June 2024.